Infinitely many solutions to the Neuman problem for quasilinear elliptic systems - Antonio Giudeppe Di Falco (Le Matematiche, 2003)
In this paper we deal with the existence of weak solutions for the Neumann problem.                                  The existence of solutions is proved by applying a critical point theorem obtained by B. Ricceri as consequence of a more general variational principle.